Molecular Phylogenetics and Population Structure of two Mahseer Species (Tor Tambroides Bleeker and Tor Douronensis Valenciennes: Cyprinidae) in Malaysia - Esa, Yuzine (2009)
This study examines the phylogenetic relationships of mahseer (genus Tor and Neolisssochillus) and their relationships with other selected cyprinids using sequence analysis of mitochondrial DNA cytochrome c oxidase I (COI) gene (464 base pairs). This study also describes the genetic structure of Tor tambroides and Tor douronensis, two important mahseer in Malaysia using both mitochondrial COI sequences and nuclear microsatellites DNA. The findings of the phylogenetic study strongly support the reciprocally monophyletic status between genus Tor (T. douronensis and T. tambroides) and genus Neolissochillus (represented by Neolissochillus stracheyi.) thus, strengthen the taxonomic status for all the three indigenous mahseer. For the other indigenous cyprinids, an interesting finding was that Barbonymus gonionotus was phylogenetically distinct from its morphologically similar species, Barbonymus schwanenfeldii (K2P distance value = 15.1%), and did not group together in a single Barbonymus clade. The population structure analysis inferred from mitochondrial COI sequences found high levels of intra and inter-population variations in T. douronensis. The presence of fixed haplotype differences among the populations, along with high FST values indicated that there has been little or no migration occur among the extant populations separated by large geographic distances, or river systems. For T. tambroides, low level of mitochondrial variations was found among the populations. The reason is probably due to the high proportion of the HKE1 haplotype found in most populations (0.736-1.000) studied except from Endau-Rompin (HKE4 is the dominant haplotype), or by the small number of samples used in the present study.